2022
DOI: 10.3389/fpsyg.2021.807887
|View full text |Cite
|
Sign up to set email alerts
|

The Generative Mechanism of Boomerang Intention: From the Perspective of Legacy Identification

Abstract: Boomerang employment has become an increasingly significant third way to obtain employees, yet little research has focused on why does ex-employee want to come back. Drawing from social identity theory, we propose that legacy identification could increase boomerang intention and both perceived corporate prestige and psychological contract violation could affect boomerang intention through legacy identification. The cooperative relationship between the former organization and the current organization could enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
(100 reference statements)
0
3
0
1
Order By: Relevance
“…These findings concur with previous research showing that identification is not related to an individual's behaviors, but rather the relationship between identification and behaviors depends on identity salience (Hogg, 2006). CRs, as a specific form of identity salience in the context of post-employment (Tian et al, 2022), moderate the relationship between LI and Ex-ECB. Therefore, these results further our understanding of the boundary conditions under which LI may foster Ex-ECB.…”
Section: Theoretical Implicationsmentioning
confidence: 96%
See 2 more Smart Citations
“…These findings concur with previous research showing that identification is not related to an individual's behaviors, but rather the relationship between identification and behaviors depends on identity salience (Hogg, 2006). CRs, as a specific form of identity salience in the context of post-employment (Tian et al, 2022), moderate the relationship between LI and Ex-ECB. Therefore, these results further our understanding of the boundary conditions under which LI may foster Ex-ECB.…”
Section: Theoretical Implicationsmentioning
confidence: 96%
“…Second, we found that psychological contract violation was negatively related to Ex-ECB. Based on the SET, when the ex-employee feels that the organization had "failed to fulfill the obligation" during employment tenure, a psychological contract violation (PCV) occurs and will persist after termination (Tian et al, 2022). This may trigger a strong negative emotional response, leading to a decrease in Ex-ECB.…”
Section: Nomological Network Of Ex-employee Citizenship Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Yeniden işe almanın artan yaygınlığına ve belirtilen faydalarına rağmen, şaşırtıcı bir şekilde literatürde az sayıda bumerang çalışanlara odaklanan çalışma bulunmaktadır (Shipp vd., 2014;Arnold, vd., 2021). Bununla birlikte, ilgili çalışmaların çoğu, bumerang çalışanlarının yeniden işe alındıktan sonraki tutum, davranış ve performanslarına odaklanmıştır (Tian, 2022). Ayrıca, bumerang istihdamı için çok şey ifade etse de bumerang niyetinin nasıl oluştuğuna dair araştırmalar da sınırlıdır (Raveendra ve Satish, 2022).…”
Section: Bumerang çAlışan Kavramıunclassified